ESPECIALLY THE ROLE OF WOMEN AND MEN IN COMMERCE (in the example of Tashkent markets in 1991-2020) - Okhunjonova Shakhodat Yusubjon kizi; Madiyeva Sitora Ikromiddin qizi (American Journals Publishing, 2023)
The article discusses the reason why the majority of the population, mainly women, became active in the 1990s trade process, what products women sell in markets and where to buy cheap products.
Keywords: Mixed markets, shuttle traders, market economy, shuttle trader.